1999
DOI: 10.1016/s0895-7061(98)00220-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and hypertension on cardiac responses to the α1-agonist phenylephrine in humans

Abstract: Both aging and hypertension decrease the responsiveness of several receptor systems. The purpose of this study was to investigate the effect of aging versus hypertension on the blood pressure (BP), heart rate, and left ventricular (LV) responses to the alpha1-agonist phenylephrine in humans. Fourteen young (age, 21-40 years; range, 30+/-1 years; mean +/- SEM), and 18 older (age, 50-73 years; range, 60+/-1 years) healthy volunteers, as well as 10 young (age, 30-39 years; range, 36+/-1 years) and 15 older (age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…4). We concluded (18) that decreased responsiveness was offset by diminished blunting by the arterial baroreflex in the hypertensive subjects (5,16). In contrast, in the present study, we show that young normotensive and hypertensive subjects show similar cardiac responses to epinephrine not only when infused alone but also when infused combined with ganglion blocker.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…4). We concluded (18) that decreased responsiveness was offset by diminished blunting by the arterial baroreflex in the hypertensive subjects (5,16). In contrast, in the present study, we show that young normotensive and hypertensive subjects show similar cardiac responses to epinephrine not only when infused alone but also when infused combined with ganglion blocker.…”
Section: Discussioncontrasting
confidence: 73%
“…aging; arterial baroflex; neuronal uptake; ␤-receptor responsiveness; heart HYPERTENSION IS GENERALLY considered to cause a decrease in cardiac ␤-adrenergic responsiveness. Hypertension also leads to blunting of counterregulatory mechanisms such as the arterial baroreflex (5,16), which also influences cardiac responses to a ␤-agonist in vivo (16). Combined with autonomic blockade, chronotropic responses to the ␤-agonist isoproterenol were not different in young normotensive and hypertensive subjects (7,18), whereas left ventricular (LV) responses showed blunting in the hypertensive subjects (18).…”
Section: Effects Of Hypertension On Cardiovascular Responses To Epinementioning
confidence: 99%
“…There are conflicting reports with regards to the effect of age on pressor responsiveness to phenylephrine. One small study (n=6 per group) that failed to rigorously screen subjects showed reduced responsiveness with aging [19], but two larger studies showed an increased blood pressure response with age, as we also demonstrated [10,20].…”
Section: Discussionsupporting
confidence: 50%
“…33 The phenylephrine infusion was started at 0.4 mg/kg/min and increased to 0.8, 1.6 and 2.4 mg/kg/min at 6 min intervals. The infusion was discontinued if SBP increased .40 mm Hg, diastolic BP increased .20 mm Hg, or the patient developed intolerable symptoms or ventricular arrhythmias.…”
Section: Phenylephrine Protocolmentioning
confidence: 99%